DAMPAK PANDEMI COVID-19 BAGI UMKM SERTA STRATEGI E-MARKETING UMKM DI INDONESIA - aldi ginting; Maria Situmorang (Universitas Quality, 2021)
The phenomenon of the Covid-19 pandemic that occurred in Indonesia not only caused health attacks but also attacked the country's economy. MSMEs as the Micro, Small and Medium Enterprises sector experienced the worst impact caused by the Covid-19 pandemic. Thus, this research is intended to see the extent of the development of the Covid-19 pandemic and how it impacts the economy in Indonesia, especially for MSMEs. Given that MSMEs are the pillars of the Indonesian economy for more than 90 percent. This research is also intended to provide an overview of e-marketing strategy solutions as short-term and long-term solutions for MSMEs. The research was conducted using a literature study technique with the result that the Covid-19 pandemic had an impact on a decline in economic growth in Indonesia. Many SMEs have had to stop their business due to various problems caused by the Covid-19 pandemic. However, the government has also issued various policies to stimulate MSMEs to survive in the midst of the Covid-19 pandemic. Various strategies are carried out, one of which is an e-marketing strategy through social media and e-commerce. The e-marketing strategy is considered to be able to help MSMEs in marketing activities and expanding the market in the midst of the Covid-19 pandemic. Through this research, the expected output is in the form of a journal.